Bovine viral diarrhea virus: Recent findings about its occurrence in pigs - de Oliveira, Luís Guilherme [UNESP]; Mechler-Dreibi, Marina L. [UNESP]; Almeida, Henrique M.S. [UNESP]; Gatto, Igor R.H. (MDPI, 2020)
Bovine viral diarrhea virus (BVDV) is an important pathogen belonging to the Pestivirus genus, Flaviviridae family, which comprises viral species that causes an economic impact in animal production. Cattle are the natural host of BVDV and the main source of infection for pigs and other animal species. Due to its antigenic and genetic similarity with other important pestiviruses such as Classical Swine Fever Virus (CSFV), several studies have been conducted to elucidate the real role of this virus in piglets, sows, and boars, not only in the field but also in experimental infections, which will be discussed in this paper. Although BVDV does not pose a threat to pigs as it does to ruminants, the occurrence of clinical signs is variable and may depend on several factors. Therefore, this study presents a survey of data on BVDV infection in pigs, comparing information on prevalence in different countries and the results of experimental infections to understand this type of infection in pigs better.
Keywords: BVDV; Experimental infection; Natural infection; Pigs